In vitro and in vivo inhibition of Daphnia magna acetylcholinesterase by surfactant agents: possible implications for contamination biomonitoring - Guilhermino, L. (2000)
This study was designed to investigate the effect of two surfactants, dodecyl benzyl sulfonate (DBS), sodium dodecyl sulfate (SDS), and of a domestic detergent (Y) on the AChE activity of the crustacean cladoceran Daphnia magna. All the chemicals significantly inhibit the activity of the enzyme, both in vitro and in vivo conditions. In vitro lowest observed effect concentration (LOEC) values ranged from 12.5 to 100 mg/l and correspondent IC50 (50% inhibition concentration) values ranged from 6.6 to 58.5 mg/l. In vivo LOEC values ranged from 2 to 11.9 mg/l, while EC50 (50% effect concentration) values ranged from 11.4 to 56.7 mg/l. AChE inhibition by environmental contaminants such as surfactants, detergents and metals may lead to false diagnostics and even wrong conclusions in biomonitoring studies based on the use of AChE as a specific biomarker for organophosphorous and carbamate compounds.